Basic Psychological Needs as Process and Content in Organismic Process Therapy (OPT): An SDT Framework for Counseling Practice - Martin F. Lynch (International Journal of Counseling and Psychotherapy, 2026)
Background: Self-Determination Theory (SDT) offers a well-established framework for understanding human motivation, psychological well-being, and maladjustment within relational contexts. Despite its strong empirical foundation, the translation of SDT into a structured counseling process model remains limited in the counseling literature. Objective: This article aims to develop Organismic Process Therapy (OPT) as a theory-grounded counseling framework that systematically translates SDT principles into a coherent therapeutic model for counseling practice. Method: Using a theoretical and conceptual analysis, this study synthesises literature from SDT, humanistic and constructivist counseling traditions, and research on motivation, trauma, attachment, and multicultural counseling to construct an integrative conceptual model. Result: The analysis proposes OPT as a counseling model in which the satisfaction of three basic psychological needs, autonomy, competence, and relatedness functions simultaneously as both the process and the content of therapy. The model is organised into three recursive phases: relational attunement, motivational clarification, and autonomy restoration, which guide counselors in facilitating autonomy-supportive therapeutic relationships. Conclusion: OPT conceptualises counseling as a relational context that restores basic psychological needs and supports clients’ movement toward volitional functioning and psychological integration. Contribution: The framework provides an integrative bridge between motivation theory and counseling practice, offering theoretical guidance for counseling practice, counselor education, and supervision while establishing a conceptual foundation for future empirical research on autonomy-supportive therapeutic processes.